'An awful state of affairs for you': managing the needs of older prisoners – a case study from the Australian Capital Territory. Issue 2 (2nd April 2020) - Jackson, Isabella; Doyle, Caroline; Bartels, Lorana
ABSTRACT: The 2013–2017 Australian Royal Commission into Institutional Responses to Child Sexual Abuse found that children were abused in over 4000 Australian institutions between 1980 and 2015. The Commission referred at least 309 matters relating to abuse in Catholic institutions to the police. It is predicted that, in the coming years, older males will comprise an increasingly large part of the prison population in Australia. High increases are already being noted in one Australian jurisdiction, the Australian Capital Territory (the ACT). This paper provides a discussion on the current experiences of older prisoners in Australia and how agencies, such as corrective services, can best address the needs of this population in the coming years.